1992
DOI: 10.1029/92jd01218
|View full text |Cite
|
Sign up to set email alerts
|

Smoke and fire characteristics for cerrado and deforestation burns in Brazil: BASE‐B Experiment

Abstract: Fires of the tropical forests and savannas are a major source of particulate matter and trace gases affecting the atmosphere globally. A paucity of quantitative information exists for these ecosystems with respect to fuel biomass, smoke emissions, and fire behavior conditions affecting the release of emissions. Five test fires were performed during August and September 1990 in the cerrado (savannalike region) in central Brazil (three fires) and tropical moist forest (two fires) in the eastern Amazon. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
180
2
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(217 citation statements)
references
References 39 publications
25
180
2
5
Order By: Relevance
“…In older work, comparisons between the CE (which correlates well with the MCE) and CH 4 EFs were presented. Ward et al (1992) showed a correlation of 0.96 and a slope of EF (CH 4 ) = −82.1 × CE + 78.6 for a regression of 18 deforestation fires in Brazil. We are not aware of any recent comparisons between MCE and EF CH 4 for fires in the extratropical forest biome, but in older work of e.g.…”
Section: Available Ef Datamentioning
confidence: 99%
“…In older work, comparisons between the CE (which correlates well with the MCE) and CH 4 EFs were presented. Ward et al (1992) showed a correlation of 0.96 and a slope of EF (CH 4 ) = −82.1 × CE + 78.6 for a regression of 18 deforestation fires in Brazil. We are not aware of any recent comparisons between MCE and EF CH 4 for fires in the extratropical forest biome, but in older work of e.g.…”
Section: Available Ef Datamentioning
confidence: 99%
“…Measurements made by Ward et al [1992Ward et al [ , 1996 in the regional haze generated by African savanna and Brazilian fires measured around 3% BC in smoldering fires and $15-20% in active flaming combustion with the exact aerosol makeup being highly dependent on the type of vegetation. However, we see that our measurements of BC in the burning season lie between these two fire regimes suggesting that the air sampled over the Darwin area contained a mix of fire plumes generated in both active and smoldering fires further inland as might be expected.…”
Section: Aerosol Compositionmentioning
confidence: 99%
“…Units were grams, nanograms or picograms (depending on the pollutant) per kilograms of consumed fuel (Andreae and Merlet, 2001). Andreae and Merlet (2001) reported that when EF is given relative to other fuel mass indicator, Finally, combustion efficiency (CE) was calculated as the ratio of released carbon in the form of CO 2 to the total mass of carbon released during combustion, according to Ward et al (1992).…”
Section: Emission Calculation and Data Analysismentioning
confidence: 99%